2021
DOI: 10.1002/vms3.701
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coagulase‐positive methicillin‐resistant Staphylococcus aureus and Staphylococcus pseudintermedius in dogs in Bangladesh

Abstract: Background The emergence of methicillin‐resistant Staphylococcus aureus (MRSA) and methicillin‐resistant Staphylococcus pseudintermedius (MRSP) have a significant health impact on people with direct or supportive occupations in veterinary medicine including veterinarians, animal handlers, laboratory personnel and pet owners. Objectives This cross‐sectional survey was conducted to determine the prevalence of and risk factors for S. aureus, S. pseudintermedius, MRSA and MRSP in dogs in Bangladesh. Methods A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Canine pyoderma is a highly prevalent bacterial skin infection in dogs, and S. pseudintermedius accounts for up to 92% of the pathogens isolated from companion dogs [ 3 ]. Studies have investigated the occurrence of MRSP colonization and contamination across diverse dog populations in different countries, with rates of up to 59% [ 3 , 35 , 36 ]. Nakaminami et al reported a high prevalence of S. pseudintermedius and MRSP in Japan, with prevalence rates of 74.5% (82/110) and 34.1% (28/82) for S. pseudintermedius and MRSP collected from pyoderma lesions, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Canine pyoderma is a highly prevalent bacterial skin infection in dogs, and S. pseudintermedius accounts for up to 92% of the pathogens isolated from companion dogs [ 3 ]. Studies have investigated the occurrence of MRSP colonization and contamination across diverse dog populations in different countries, with rates of up to 59% [ 3 , 35 , 36 ]. Nakaminami et al reported a high prevalence of S. pseudintermedius and MRSP in Japan, with prevalence rates of 74.5% (82/110) and 34.1% (28/82) for S. pseudintermedius and MRSP collected from pyoderma lesions, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of MRSP identified based on mecA was 6.58% (10/152); Rana et al reported prevalence rates of 45.3% and 6% for S. pseudintermedius and MRSP in dogs in Bangladesh, respectively. All isolated bacteria were resistant to more than three antimicrobial classes [ 35 ]. MRSP prevalence in S. pseudintermedius isolated in this study was 1.5 times lower than that previously reported by Jantorn et al in Thailand in 2021 (18.87%, 10/53 vs. 28.30%, 15/53) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to coagulase-negative staphylococci, CPS may result in more severe infections [ 29 , 30 ]. A great many prior investigations have demonstrated that S. pseudintermedius is a prevalent cause of canine pyoderma [ 29 , 31 , 32 ]. In a recent investigation, all examined isolates were conventionally identified as CPS.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the isolates of S. pseudintermedius exhibited resistance to tetracycline (96.6%), erythromycin (79.3%), and chloramphenicol (37.9%), but were sensitive to the quinolones. A study in Bangladesh found that 84.7% of S. pseudintermedius strains were resistant to erythromycin, and 6% of isolated strains were MDR ( 59 ). In the present study, 24.1% of the isolates were defined as the MDR S. pseudintermedius phenotype, and there was a larger percentage in the dogs with keratitis compared with in the healthy dogs.…”
Section: Discussionmentioning
confidence: 99%